Micro/nano-net guides M2-pattern macrophage cytoskeleton distribution via Src–ROCK signalling for enhanced angiogenesis. (16th March 2021) - Yang, Yang; Lin, Yujing; Zhang, Zhengchuan; Xu, Ruogu; Yu, Xiaoran; Deng, Feilong
Abstract : Macrophages exhibit an M2-pattern cytoskeleton and promote angiogenesis on the micro/nano-net. Abstract : Implant surface topography has been proven to determine the fate of adhered macrophage polarization, which is closely related to the cytoskeletal arrangement during adhesion. Our purpose was to establish a topography that is favourable to M2 macrophage switching by regulating macrophage cytoskeleton distribution. Two micro/nano-net structures with different pore sizes were generated by alkali bathing at medium (SAM) or high (SAH) temperature based on the micro-level surface. Their surface characteristics, in vitro macrophage polarization and impact on endothelial cells were analysed. The in vivo macrophage response and osseointegration were also tested. The results showed that the micro/nano-net has high hydrophilicity and moderate roughness. In the SAH and SAM groups, macrophages exhibited an elongated cytoskeleton with tiny protrusions and had a high M2/M1 polarization ratio with enhanced angiogenic ability, and in vivo studies also showed faster angiogenesis and bone formation in these groups. SAH showed even better results than SAM. For cytoskeleton related pathway explanation, ROCK expression was upregulated and Src expression was downregulated at the early or late adhesion stage in both the SAH and SAM groups. These results indicated that the micro/nano-net structure guides elongated macrophage adhesion states via Src–ROCK signalling and switches macrophages towards the M2 phenotype, which provides a cytoskeleton-oriented topography design for an ideal immune response.